2022
DOI: 10.3389/fphar.2022.1038043
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis and pericarditis associated with SARS-CoV-2 vaccines: A population-based descriptive cohort and a nested self-controlled risk interval study using electronic health care data from four European countries

Abstract: Background: Estimates of the association between COVID-19 vaccines and myo-/pericarditis risk vary widely across studies due to scarcity of events, especially in age- and sex-stratified analyses.Methods: Population-based cohort study with nested self-controlled risk interval (SCRI) using healthcare data from five European databases. Individuals were followed from 01/01/2020 until end of data availability (31/12/2021 latest). Outcome was first myo-/pericarditis diagnosis. Exposures were first and second dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…In the study of Bots et al-a populationbased descriptive cohort and a nested self-controlled risk interval study using 5 European databases that included over 35 million individuals-the authors concluded the myocarditis rates were elevated in individuals less than 30 years old after both doses of the Pfizer vaccine and the second dose of the Moderna vaccine. 28 In our case report, myocarditis was unlikely, as the patient did not have chest pain, and the electrocardiogram was normal.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the study of Bots et al-a populationbased descriptive cohort and a nested self-controlled risk interval study using 5 European databases that included over 35 million individuals-the authors concluded the myocarditis rates were elevated in individuals less than 30 years old after both doses of the Pfizer vaccine and the second dose of the Moderna vaccine. 28 In our case report, myocarditis was unlikely, as the patient did not have chest pain, and the electrocardiogram was normal.…”
Section: Discussionmentioning
confidence: 55%
“…In rhabdomyolysis cases, cardiac involvement must be considered, as many myocarditis and pericarditis have been reported. In the study of Bots et al—a population‐based descriptive cohort and a nested self‐controlled risk interval study using 5 European databases that included over 35 million individuals—the authors concluded the myocarditis rates were elevated in individuals less than 30 years old after both doses of the Pfizer vaccine and the second dose of the Moderna vaccine 28 …”
Section: Discussionmentioning
confidence: 99%
“…The risk interval was defined as days 1 to 28 after PPSV23 vaccination, while the control interval was defined as days 57 to 112 after PPSV23 vaccination, with day 0 defined as the day of PPSV23 vaccination. The adoption of a 28-day risk period aligns with previous studies investigating the cardiovascular, neurological, or immunological events associated with vaccination . We excluded outcomes that occurred on the day of vaccination to account for the possibility of reverse causation, unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Our hypotheses regarding the extent of bias can be seen in Table 1when the assumption of event-dependent exposures is violated. (10), and have been described in greater detail in previous publications (11).…”
Section: (C) Standard Sccsmentioning
confidence: 99%
“…The core methods have been previously described (11). Briefly, individuals who experienced both the outcome of interest and were vaccinated between 1 September 2020 and the end of data availability (which varied in the different databases) were eligible for inclusion.…”
Section: Study Design and Analysismentioning
confidence: 99%